SUBSEA PIPELINE DESIGN AND ANALYSIS IN BERHALA STRAIT WATERS - Abhirama Kanantyo, Muhammad
The process of fulfilling the demand of oil and gas can be done by doing exploration and exploitation. These activities can happen on both land and sea. When these activities are being performed under the sea, subsea pipeline systems are needed to deliver oil and gas from the ocean to the land. Indonesia, as a country with 2/3 of it covered by ocean, has a lot of potential to explore and exploit oil and gas underneath the ocean floor. According to the statistical data released by Energy and Mineral Resource Ministry in 2023, Central Sumatera and South Sumatera rank first and third place for provinces with the highest oil reserve in Indonesia. Central Sumatera has 1410.34 million barrel of oil, while South Sumatera has 601.50 million barrel of oil. Each of those numbers consist of 3 types of oil reserve, which are proven, probable, and possible oil reserve. The datas released by Energy and Mineral Resource Ministry support the location where subsea pipeline is designed and analysed. Location where this undergraduate thesis takes place is the Berhala Strait Waters, on the east of Sumatra Island. In this undergraduate thesis, the designed subsea pipeline spreads 268 kilometers across the ocean, from Kuala Tungkal to a platform in the middle of the South China Sea. The processes of designing and analysing this subsea pipeline are done with the help of international standards. The processes of designing and analysing this subsea pipeline consist of collecting and processing the environmental data, wall thickness analysis, on-bottom stability analysis, subsea pipeline installation analysis, and free span analysis. Collecting and processing the envinronmental data results in environmental data for specific return periods (1-year, 10-year, and 100-year return periods) which then get used as one of the input data for the analytical processes after that. Wall thickness analysis is done using DNV-ST-F101 as the guide/reference. This analysis results in 12.7 mm as the thickness of steel pipe used in this undergraduate thesis. On-bottom stability analysis is done using DNV-RP-F109 as the guide/reference. This analysis results in 62 mm as the thickness of concrete coating used in this undergraduate thesis. Subsea pipeline installation analysis with S-lay method is done using DNV-ST-F101 as the guide/reference. The result of this analysis is the lay barge’s roller and stinger configurations. Lastly, free span analysis is done using DNV-RP-F105 as the guide/reference. This analysis results in 13.3 m as the maximum free span allowed used in this undergraduate thesis.